Creative Teaching Training for Kindergarten and Elementary School Teachers in Suli District, Luwu - Rahman, Indah Fadhilah; Asmawati, Andi; Nursanti; Ahmad, Ardi; Haerat, Ahmiranil; Juleha, Juleha (IJOCSE: Indonesian Journal of Community Services, 2023)
The community service program is one part of the Tridharma of higher education. Therefore it is an obligation for every lecturer and other academics to be involved in community service programs. The long-term goal of this community service program is to develop a mentoring-based creative learning for kindergarten and elementary school teachers. Specifically, the objectives to be achieved are 1) To provide an explanation of learning models that can be applied to kindergarten and elementary school students. 2)Improve the ability of educators in designing, managing, and implementing active, innovative, creative, effective and fun learning. The method used in an effort to achieve this goal is in the form of several preparatory stages, namely: 1) Discussing with students of Community Service Program 71 post 3 of Botta village about teaching techniques for kindergarten and elementary school teachers. 2) Determining the implementation time, 3) Preparing training materials, 4) Outreach to prospective training participant teachers. The results of this program show that the training participants were very enthusiastic and responded well, in which one of the participants stated that they really needed training for self-development, and the participants in this activity hoped that there would be further activities in the future to come.